DESENVOLVIMENTO DE UM CARRO PARA COMPETIÇÕES FORA DE ESTRADA “OFF-ROAD” - BONFADA, ANDERSON R.; KAFKA, DAVID; ABENTROTH, FERNANDO H.; STAM, JOAO G.; BARBIERI, JOAO R. P.; CARPES, JONATAS V.; HEIMBURG, JULIO C. V.; DANETTE, LUCAS I.; BATAGLIN, MARCELO; BENATTI, MATEUS; et al. (Salão do Conhecimento, 2013)
Resumo